Earning Management Actions and Conditional Revenue as Managerial Efforts to Maintain Bond Rating - Andriawan Andriawan; Ignatius Roni Setyawan (The Indonesian Journal of Accounting Research, 2020)
The purpose of this study is examine the analysis of factors affecting Bonds rating of non-financial companies listed on Indonesia Stock Exchange for the period 2012-2016. Sample was selected using purposive sampling method amounted to 30 companies. Data processing techniques using multiple regression analysis what helped by SPSS program. The result of this study shows that partially company’s size, company’s growth, and auditor size have significant influence on bonds rating, while the earnings management have no significant effect on bonds rating. This result supports the Heintz (2017) study that management will think twice about earnings management when rating bonds. This is based on the principle of transparency in corporate governance that the actual company's performance will better reflect the company's position as a good bond issuer. However, this study shows that company’s size, company’s growth, and auditor size have a significant effect on bonds rating respectively. This result proves once again that in determining the bond rating, the factor of firm size, growth and auditor size are very important factors in bond rating. Without having to do earnings management then if the company has good size, growth and auditors size related then it will also be good to bond ratings according to the criteria of these rating providers.